2006
DOI: 10.1108/09685220610678622
|View full text |Cite
|
Sign up to set email alerts
|

Practices and problems in managing electronic services using SLAs

Abstract: PurposeThe aim of this paper is to present the key areas of activity to be used for drafting service level agreements (SLAs) for electronic services and, at the same time, to present best practices and problems that arise from the application of this discipline.Design/methodology/approachA range of recently published (2000‐2005) works has been reviewed, in order to: a) analyse how an SLA has to be defined and applied b) identify the applicable best practices and c) identify the problem areas.FindingsProvides g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…She identified five problems with how SLAs were used in those interactions, three of which are particularly relevant. A 2008 Forrester Research study [10] and a paper identifying SLA principles and best practices by Fitsilis [11] support her conclusions and offer additional problems, as follows:…”
Section: Service Level Agreementsmentioning
confidence: 95%
See 2 more Smart Citations
“…She identified five problems with how SLAs were used in those interactions, three of which are particularly relevant. A 2008 Forrester Research study [10] and a paper identifying SLA principles and best practices by Fitsilis [11] support her conclusions and offer additional problems, as follows:…”
Section: Service Level Agreementsmentioning
confidence: 95%
“…A Forrester study [10] concluded most SLAs are defined in technical terms not accessible to business users. Fitsilis [11] emphasizes the difficulty in mapping service levels from low-level measurable information to higher-level meaningful information, reporting that only technical specialists understand SLAs. He also emphasizes the importance of changing this: the first two best practices identified are "service level definitions should be business-based, meaningful to the users..." and "service level definitions should be easily defined and measurable".…”
Section: Service Level Agreementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The service provider may be an internal IT/IS department, or the provision may be outsourced from an outside opera- tor. Outsourcing continues to grow as a business practice when ASP, Web hosting or other such services become more popular (Fitsilis, 2006).…”
Section: Contemporary Issues In Management Of Eucmentioning
confidence: 99%
“…Although there is much evidence with regard to the advantages of SLAs in IT service management, research has identified major problems in applying them (Antonio, Arienzo, Esposito et al, 2004;Hiles, 1994;Trienekens, Bouman, & Van Der Zwan, 2004). Fitsilis (2006) categorizes these problems in two areas: problems related with traditional service level management, such as developing SLA semantic models; cost models; better understanding of SLA terms, and so forth; and problems that arise from technology and marketplace evolution such as SLAs for federated environments, for aggregated services and for on-demand services, and so forth. Trienekens et al (2004) explain that the problems arise from SLA specifications: specification of effort versus specification of results, or unclear service specifications.…”
Section: Contemporary Issues In Management Of Eucmentioning
confidence: 99%